(untitled) (Archives of Criminology, 2023)
Persons deprived of their liberty in penitentiary institutions are among the groups most exposed to SARS-CoV-2 infection. One of basic ways to limit the development of the epidemic in these institutions is to reduce the number of prisoners. The first case of COVID-19 was diagnosed in Poland on 4 March 2020. Unlike in some European countries, after the outbreak of the COVID-19 pandemic, there was no preventive release of prisoners in order to limit the spread of SARS-CoV-2 in prisons. In March 2020, the Polish parliament passed legal provisions which introduced a special break in the enforcement of prison sentences due to the epidemic threat and widened the possible use of electronic monitoring as an alternative way to serve prison terms. These new solutions did not contribute to a significant increase in the number of prisoners released from prisons. In the period from March to December 2020, the prison population in Poland dropped by more than 10%, however, this mainly resulted from a reduced number of admissions to penitentiary institutions. The article discusses the limitations of the use of particular measures in order to reduce the overall number of prisoners.